FACTORS INFLUENCING PONZI SCHEME PARTICIPATION IN NIGERIA - Obamuyi, Tomola Marshal; Iriobe, Grace Oluwabukanla; Afolabi, Taofeek Sola; Akinbobola, Akinpelu Denis; Elumaro, Adegboyega John; Faloye, Bukola Akintade; Adeyefa, Ademola Felix; Adepoju, Titilope Francis; Oni, Anthonia Olabisi (Advances in Social Sciences Research Journal, 2018)
This study examined the factors influencing Ponzi scheme participation in Nigeria. A multi-stage sampling procedure was used to select 384 participants for the study. Descriptive statistic and One-Way ANOVA was employed to analyze the data. The result of the analysis revealed that friends’ recommendation, expected benefits, current economic situations, ease of obtaining funds and the get rich quick syndrome were the most influencing factors on Ponzi scheme participation and these factors were significant with the gender, age, marital status, employment status and educational level at 5% level of significance. The study concluded that ponzi scheme participation was mostly influenced by friend’s recommendation, expected benefit, current economic situations, ease of obtaining funds and the Get rich quick syndrome. Therefore, the study recommended that the Nigerian government should integrate Ponzi schemes into the Nigerian financial system and subject them to the country’s regulatory environment to minimize the consequences of future failure of the schemes.